2003
DOI: 10.1038/sj.cdd.4401330
|View full text |Cite
|
Sign up to set email alerts
|

VEIDase is a principal caspase-like activity involved in plant programmed cell death and essential for embryonic pattern formation

Abstract: Plant embryogenesis is intimately associated with programmed cell death. The mechanisms of initiation and control of programmed cell death during plant embryo development are not known. Proteolytic activity associated with caspase-like proteins is paramount for control of programmed cell death in animals and yeasts. Caspase family of proteases has unique strong preference for cleavage of the target proteins next to asparagine residue. In this work, we have used synthetic peptide substrates containing caspase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
95
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 45 publications
2
95
1
1
Order By: Relevance
“…Proteolytic activity of recombinant mcII-Pa and P. abies cell extracts (16) were assayed in 150-l reaction mixtures containing 0.3 g of recombinant protein or 22.5 g of total protein, respectively, and 50 M individual substrate in the optimized assay buffer: 100 mM Hepes, pH 7.0͞50 mM CaCl 2 ͞0.1% 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate͞5 mM DTT (Fig. 7, which is published as supporting information on the PNAS web site).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteolytic activity of recombinant mcII-Pa and P. abies cell extracts (16) were assayed in 150-l reaction mixtures containing 0.3 g of recombinant protein or 22.5 g of total protein, respectively, and 50 M individual substrate in the optimized assay buffer: 100 mM Hepes, pH 7.0͞50 mM CaCl 2 ͞0.1% 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate͞5 mM DTT (Fig. 7, which is published as supporting information on the PNAS web site).…”
Section: Methodsmentioning
confidence: 99%
“…7, which is published as supporting information on the PNAS web site). First-order kinetics of substrate cleavage was measured as described (16). For each independent experiment, at least three assays were performed, each assay containing triplicate reactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SI-induced caspase-3-like/DEVDase exhibits maximum substrate cleavage in vitro at pH 5, with peak activity 5 h after SI induction in vivo (Bosch and Franklin-Tong, 2007). The low pH optimum for this caspase-3-like/DEVDase activity is unusual, because most of the cytosolic plant caspase-like activities identified to date have optimal activity close to normal physiological pH (approximate pH, 6.5-7.0; Korthout et al, 2000;Bozhkov et al, 2004;Coffeen and Wolpert, 2004). Because the SI-induced cytosolic-located DEVDase requires a low pH for activity, this suggested that, during SI, the pollen tube cytosol undergoes dramatic acidification.…”
mentioning
confidence: 99%
“…There is considerable biochemical evidence for the involvement of caspase-like activities in plant PCD (van Doorn and Woltering, 2005). For example, the vacuolar processing enzyme has YVADase (caspase-1-like) activity (Hatsugai et al, 2004;Rojo et al, 2004;Hara-Nishimura et al, 2005), DEVDase (caspase-3-like) and YVADases are associated with PCD in several plant systems (del Pozo and Lam, 1998;Korthout et al, 2000;Danon et al, 2004), and VEIDase (caspase-6-like) is the main caspase-like activity involved in embryonic pattern formation (Bozhkov et al, 2004). However, because plants have no caspase gene homologs (Sanmartín et al, 2005), the nature of their caspase-like enzymes is the subject of considerable debate.…”
mentioning
confidence: 99%